Perbandingan Metode Depth of Field pada Lensa Kamera Fotografi dengan Efek Lensa pada Software Animasi - Ahmad Faisal Choiril Anam Fathoni; Dermawan Syamsuddin (Humaniora, 2013)
The knowledge of photography becomes fundamental importance in the understanding of digital cinematography. The work of a good photography is a blend of knowledge and photographic ability (skill) correctly. By learning photography properly, it allows an animator or digital art workers to apply some standard cinematography as well. By knowing the comparison between photography with "photographic" in 3D animation, animators will be easier to create a digital aesthetic standard with the help of the software. This paper discusses the comparison of the use of photographic camera lenses and camera parameters found in animation software 3D Studio Max. The final form is the camera pictures and parameters of used lens with the results of rendering images with the software-related parameter.